NARRATE: Digital Recording and Documentation of Ecclesiastical Cultural Treasures in Monasteries and Temples (the Project Activities in Bulgaria) - Kaminis, Ioannis (Forum Theologicum Sardicense, 2025)
The project was initiated by a group of scientists from the Aristotle University of Thessaloniki in 2022. It was later joined by scientists from Sofia University “St. Kliment Ohridski,” the Association for the Protection of Cultural Heritage of the Republic of Turkey, the Hellenic Open University, and the German IT company Cognitiv Ex. The project’s activities are focused on the region of Thrace, which spans Bulgaria, Turkey, and Greece. Since Late Antiquity, this region has been the object of the mission of the Church, resulting in a vast Christian cultural heritage.